Traumatic Dental Injuries: Clinical Case Presentation and a 10-Year Epidemiological Investigation in an Italian Dental Emergency Service - Alberto Murri Dello Diago; Luigi Generali; Roberto Apponi; Vittorio Colombini; Vittorio Checchi (Case Reports in Dentistry)
Traumatic dental injuries (TDIs) are very common in the world population, and international literature reports several studies which helped in the definition of international guidelines. The aim of this study is to present two clinical cases of TDI and to investigate epidemiological and etiological aspects of TDIs in patients treated in Modena, Italy, between January 2010 and December 2020. The presented case reports are two explicative clinical cases of successful TDI management with a long-term follow-up. The epidemiological analysis was performed on patients who visited the Dental Emergency Service of the Dentistry and Oral-Maxillo-Facial Surgery Unit of Modena (Italy) over a period of 10 years. Data relating to age, gender, type of trauma, and place of accident were collected. Five-hundred-sixty-five TDIs that occurred to patients from 1 to 68 years old were reported, with a total of 860 injured teeth. The peak age at which TDIs are most represented varies between 2 and 3 years old, and they occurred frequently from 1 up to 7 years old. 57.5% were male, while 42.5% were female. The most common trauma resulted to be the uncomplicated crown fracture (20%), immediately followed by lateral luxation (19%), intrusive luxation (18%), avulsion (17%), and complicated crown fracture (15%). TDIs occurred at home in 44% of cases. The need for more prevention training must be highlighted, due to the fact that many TDIs occur at home and in a preschool age.